2005
DOI: 10.1093/eurheartj/ehi196
|View full text |Cite
|
Sign up to set email alerts
|

Impedance compensated biphasic waveforms for transthoracic cardioversion of atrial fibrillation: a multi-centre comparison of antero-apical and antero-posterior pad positions

Abstract: The influence of pad position for DCC of AF may be less pertinent with ICB waveforms than with monophasic waveforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 29 publications
2
49
1
5
Order By: Relevance
“…Though our data are from a single center, the considerable variability in starting energy and shock energy escalation suggests nonuniform practices, which is consistent with the variability in ECV techniques seen at other centers . Furthermore, our findings were similar in sensitivity analyses restricted to patients who received ≥150 J for their first shock, which has been the suggested starting energy by others . We used data from biphasic truncated exponential (BTE) waveform defibrillators only.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Though our data are from a single center, the considerable variability in starting energy and shock energy escalation suggests nonuniform practices, which is consistent with the variability in ECV techniques seen at other centers . Furthermore, our findings were similar in sensitivity analyses restricted to patients who received ≥150 J for their first shock, which has been the suggested starting energy by others . We used data from biphasic truncated exponential (BTE) waveform defibrillators only.…”
Section: Discussionsupporting
confidence: 74%
“…Contemporary defibrillators deliver biphasic shocks and modify their waveforms in response to the measured TTI. Indeed, in contrast to studies using monophasic shocks, 2 publications reporting on biphasic waveforms in patients with ventricular tachyarrhythmias found that TTI was not predictive of shock success …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This position is the most widely used in clinical practice and has been previously shown to be as effective as anteroposterior pad positions when using an impedance-compensated biphasic waveform 15. The transthoracic impedance for each shock was recorded by the defibrillator.…”
Section: Methodsmentioning
confidence: 99%